Substituting fishmeal with napier grass protein: effects on intake, growth performance and carcass characteristics of broiler chickens - Kiggundu, A.M.; Nampijja, Z.; Kigozi, A.; Mugerwa, S.; Molly, A.; Namazzi, C.; Kayondo, S.I.; Walugembe, F.; Bombom, A. (2025)
This study evaluated the performance and carcass characteristics of broiler chickens fed diets with varying substitution levels of fishmeal (FM) 0 g/kg, 250 g/kg, 500 g/kg, 750 g/kg, and 1000 g/kg DM with Napier grass protein (NGP). Treatment diets included T0 (control diet), T250, T500, T750, and T1000 to represent the different substitution levels. After the starter phase, birds were finished on a conventional fishmeal-based diet for 14 days. Feed intake, weight gain, and hot carcass decreased (P < 0.01) at a decreasing rate with increasing substitution in starter diets. Feed intake, weight gain, and hot carcass were highest (P < 0.01) in T0 birds, followed by T250 birds. Feed conversion ratio (FCR), protein, and energy utilization efficiencies were highest (P < 0.01) in T0 birds, followed by T250 birds, and lowest for T1000 birds. Ileal CP digestibility (862.3 g/kg DM) was highest for T0 birds but comparable (P > 0.05) to T500 birds (716.4 g/kg DM). Similarly, ME digestibility was highest in T0 birds (819.5 g/kg DM) although comparable (P > 0.05) to T250 birds and T500 birds. In contrast, T250 and T500 birds showed higher (P < 0.05) crude fiber digestibility (645 g/kg DM) than T0 birds (402 g/kg DM). Hot carcass weight decreased (P < 0.01) with FM substitution with the heaviest carcasses recorded for T0 birds. As a percentage of the hot carcass, the weight of the breast and thigh reduced (P < 0.05) with increasing substitution of FM. Percentage weights of empty gizzard, caeca, and pancreas for T1000 birds were higher (P < 0.05) and double compared with T0 birds. In the finisher phase, there was no difference (P > 0.05) in weight gains of T0 and T250 birds, although T250 birds had numerically higher weight gain compared with T0 birds. However, the percentage change in weight gain in the finisher phase was influenced (P < 0.05) by the MFP substitution level in the starter phase. In the finisher phase, T1000 birds had the highest percentage change in weight gain (71.6%) compared to 40.7% for T0 birds. Nonetheless, regression analysis of FCR data in the starter phase showed that optimal FCR is attained at 150 g/kg NGP substitution in broiler diets. These results suggest that NGP is of low biological value in broiler diets, probably due to its high fiber content and deficiency in methionine and lysine, which are limiting essential amino acids in broiler diets.